Examination of Executive Factors Influencing Social Media Policies in Providing Electronic Services in Private Banks - Izadimanesh, Fatemeh; Norouzi Mobarakeh, Ali; Askari, Ahmad (Management Strategies and Engineering Sciences, 2023)
Policymaking in electronic banking, due to its dynamic nature and heavy reliance on information technology, is more sensitive compared to other industries. This study examines the role of social media in delivering electronic services to customers of private banks. This research is applied in its objective, qualitative in methodology, and employs grounded theory as the research method. Its nature is exploratory-descriptive, data collection is conducted through interviews, and data analysis utilizes the three-phase coding approach of grounded theory. The statistical population includes managers and experts in the private banking industry with comprehensive knowledge of social media marketing. From this population, 12 participants were selected for semi-structured interviews using a purposive snowball sampling method. Appropriate codes were initially assigned to different sections of the data, and concepts were identified. Finally, through selective coding, categories were refined, and the primary dimensions of the study were delineated as causal, central, contextual, intervening conditions, strategies, and outcomes. The findings revealed that electronic services, encompassing electronic service quality and electronic service recovery quality, are causal factors influencing electronic banking. Electronic banking, through information dissemination, communication, and transactions, leads to customer satisfaction and impacts their perceived value. Additionally, social media policies, via adoptability and social interactions, serve as intervening conditions that influence customer satisfaction and perceived value. Moreover, infrastructure, including security and technical infrastructure, acts as a governing context that affects the phenomenon under study (perceived value). Ultimately, this results in customer loyalty and the creation of value for both customers and banks. Overall, the findings of this study indicate that social media policies in electronic banking are significantly influenced by electronic services. However, social media and infrastructure can directly and indirectly impact these influences.